2002
DOI: 10.1128/aem.68.6.2910-2916.2002
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Membrane Fatty Acid Composition of Resistant or Susceptible Leuconostoc or Weissella Strains in the Presence or Absence of Mesenterocin 52A and Mesenterocin 52B Produced by Leuconostoc mesenteroides subsp. mesenteroides FR52

Abstract: Mesenterocins 52A (Mes52A) and 52B (Mes52B) are antimicrobial peptides produced by Leuconostoc mesenteroides subsp. mesenteroides FR 52. Mes52A is a class IIa bacteriocin of lactic acid bacteria with a broad spectrum of activity. Mes52B is an atypical class II bacteriocin with a narrow spectrum of activity. Four Leuconostoc and Weissella wild-type strains were selected for their susceptibility or insensitivity to these mesenterocins. Four strains resistant to Mes52A or Mes52B were generated from the three susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 31 publications
4
22
0
Order By: Relevance
“…They observed saturated (C12:0, C14:0, C16:0, C18:0, C19:0) and unsaturated fatty acids (C16:1and C18:1) as major composition of membrane fatty acids in mundticin KS sensitive and resistant mutants of E. faecium and also reported significant reduction in unsaturated fatty acids and increase in saturated fatty acids in the muditicin KS resistant mutants than in wild type strains of E. faecium. Decrease in membrane fluidity has also been reported in L. monocytogenes against nisin (Mazotta and Montville, 1997; Li et al, 2002) and in Leuconostoc or Weisella strains against mesentericin 52A and 52B (Limonet et al, 2002). There were significant increase in saturated fatty acids (10% more) and reduction in unsaturated fatty acids (6% less) of mesentericin 52A and 52B resistant mutants of Leuconostoc species making their membrane more rigid when compared to wild type strains.…”
Section: Discussionmentioning
confidence: 72%
“…They observed saturated (C12:0, C14:0, C16:0, C18:0, C19:0) and unsaturated fatty acids (C16:1and C18:1) as major composition of membrane fatty acids in mundticin KS sensitive and resistant mutants of E. faecium and also reported significant reduction in unsaturated fatty acids and increase in saturated fatty acids in the muditicin KS resistant mutants than in wild type strains of E. faecium. Decrease in membrane fluidity has also been reported in L. monocytogenes against nisin (Mazotta and Montville, 1997; Li et al, 2002) and in Leuconostoc or Weisella strains against mesentericin 52A and 52B (Limonet et al, 2002). There were significant increase in saturated fatty acids (10% more) and reduction in unsaturated fatty acids (6% less) of mesentericin 52A and 52B resistant mutants of Leuconostoc species making their membrane more rigid when compared to wild type strains.…”
Section: Discussionmentioning
confidence: 72%
“…Recently, resistance to class IIa bacteriocins has been reported. For example, Limonet et al (2002) reported variations in fatty acid composition of mutants of Leuconostoc and Weissela strains resistant to the class IIa bacteriocin mesenterocin 52A (Mes 52A). They showed that resistant strains contained more saturated fatty acids when cultured with Mes 52A.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Limonet et al (2002) reported variations in fatty acid composition of mutants of Leuconostoc and Weissela strains resistant to mesenterocin 52A (Mes 52A). We have also found differences in fatty acid (Table 1) and phospholipid contents (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…This increased fluidity of the bacterial cell membrane did not allow alamethicin to form stable pores in the phospholipid bilayer. A decrease in membrane fluidity has been reported in L. monocytogenes against nisin (11) and in Leuconostoc and Weisela strains against mesentericin 52A and 52B (12). The decrease in the total BCFA of Alm r variants led to increased membrane rigidity, as their main role in bacteria is to increase fluidity.…”
Section: Discussionmentioning
confidence: 99%